Bridging Disciplinary Expertise and Innovative Instructional Design: A Bibliometric Mapping of Socio-Scientific Issues (SSI) Trends - Dian Darliana; Asri Widowati (Assyfa Learning Journal, 2026)
Effective science education requires bridging disciplinary expertise with innovative instructional design, yet how Socio-Scientific Issues (SSI) are integrated into modern learning ecosystems remains fragmented. This study aims to map global research trends, thematic structures, and emerging gaps in SSI within science education through a comprehensive bibliometric approach to inform future pedagogical designs. Using Publish or Perish, a dataset of 1,000 articles published between 1958 and 2026 was retrieved, accumulating 330,947 citations. Co-occurrence analysis was conducted using VOSviewer on 5,504 identified terms, selecting 80 highly relevant terms grouped into four main thematic clusters representing social-policy issues, science education, conceptual foundations, and methodological approaches. Network visualization revealed science education as the central node connecting multidisciplinary themes, while overlay visualization demonstrated a clear temporal shift from early theoretical studies toward student-centered instructional practices and scientific literacy. Critically, density visualization exposed significant research gaps, including the limited integration of SSI into concrete instructional designs, insufficient focus on value-based dimensions, and a lack of context-specific practical implementations. This study concludes that to advance the Scholarship of Teaching and Learning (SoTL), future research must transition from descriptive data mapping to the creation of actionable, context-based instructional design models that effectively translate SSI into classroom practice, thereby enhancing students' scientific literacy and critical decision-making competencies within complex learning environments.